Suicidal Ideation Predicts Functioning and Quality of Life Over One Year after Acute Coronary Syndrome - Kim, Jae-Min (Psychiatry Investig, 2019)
OBJECTIVE: This study investigated the associations of suicidal ideation (SI) evaluated within 2 weeks after an acute coronary syndrome (ACS) episode with functioning, disability, and quality of life (QOL) at a 1-year follow-up assessment. METHODS: This study recruited 1152 consecutive patients within 2 weeks of a confirmed ACS episode; 828 of these patients who were followed up 1 year later comprised the study sample. SI was determined at baseline using the “suicidal thoughts” item of the MontgomeryÅsberg Depression Rating Scale. At both examinations, social and occupational functioning were measured by the Social and Occupational Functioning Assessment Scale (SOFAS), disability was estimated by World Health Organization Disability Assessment Schedule-12 (WHODAS-12), and QOL was assessed using the World Health Organization Quality of Life-Abbreviated form (WHOQOL-BREF). Baseline covariates included sociodemographic data, depression characteristics, cardiovascular risk factors, and current cardiac status. RESULTS: SI at baseline was independently associated with less improved or decreased scores on the SOFAS, WHODAS-12, and WHOQOL-BREF over 1 year after adjusting for relevant covariates. CONCLUSION: SI within 2 weeks of an ACS episode predicted poorer functioning and QOL at a 1-year follow-up assessment. Thus, the simple evaluation of SI in patients with recently developed ACS could be helpful in screening for functioning and QOL during the chronic phase of this disease.